A record ammonia adsorption by calcium chloride confined in covalent organic frameworks. Issue 8 (4th January 2022) - Tian, Xiaoxin; Qiu, Jikuan; Wang, Zhenzhen; Chen, Yongkui; Li, Zhiyong; Wang, Huiyong; Zhao, Yuling; Wang, Jianji
Abstract : CaCl2 @COF hybrid materials have been designed and prepared to exhibit a record capacity for ammonia capture and excellent recyclability. Abstract : Ammonia is a vital chemical raw material, but it is also a highly toxic environmenal pollutant. However, its highly efficient uptake and reversible release is a challenge. Herein, we have designed and synthesized a series of hybrid materials for efficient NH3 capture by confining calcium chloride (CaCl2 ) in a porous covalent organic framework (COF). A high capture capacity of 26.5 mmol g −1 is obtained at 25 °C and 1 bar, which is the highest value among existing porous materials, and NH3 can be easily desorbed at 80 °C under vacuum for 2 h. Particularly, the hybrid COF is highly efficient for the absorption of low NH3 content. Such excellent performance is ascribed to the highly dispersion of CaCl2 in the pores of the COF, and coordinating interaction of NH3 to Ca 2+ together with hydrogen bond interaction between NH3 and Cl − .